Criticisms in Urdu Literature in the Context of “Savera ” Magazine - Zarghona Kanwal; Hakan Kuyumcu (Şarkiyat Mecmuası)
This study has been organised to examine the literary criticism of writers who participated in the Progressive Writers’ Association and Halqa-e Arbab-e Zouq between 1947 and 1974 in Savera, the leading journal of the Progressive movement in Pakistan. Savera became one of the most important journals in which a large number of Marxist and leftist writers published their literary and political thoughts. It also contributed to the publication of articles containing literary criticism of Urdu writers within the Progressive Writers’ Movement andHalqa-e Arbab-e Zouq. The journal covered a wide range of literary and cultural articles, criticism, biographies and works of writers. This reflected the journal’s commitment to providing a platform for a variety of intellectual discourses covering both literary and political dimensions. Savera’s literary criticism section has played an important role in stimulating intellectual debate on the purpose and role of literature in Pakistan. The magazine’s diverse perspectives and rich content have contributed to making it a platform for new writers and poets such as Saadat Hasan Mantu, Mumtaz Shirin, Ali Sardar Jaafari, Miraji and Ehtisham Hussain. These writers helped establish literary criticism as a distinct genre. Pakistan’s cultural identity was significantly influenced by this journal, which facilitated the dissemination of the works of writers from different ethnic backgrounds and served a function for literary and cultural exchange.